Emerging or newly discovered viral causes of acute lower respiratory tract infections worldwide - Venter, Marietjie; Hellferscee, Orienka (Henry Stewart Talks, 2013)
Lower respiratory infections, Global distribution of mortality among children, Community-acquired pneumonia in children, Causes of severe acute respiratory infections, The three classifications of viruses, Zoonosis: new viruses – Coronaviruses and SARS, Avian influenza, Hendra virus, Nipah virus, Emergence of new zoonotic viruses, Newly recognized causes of ALRI – Rhinovirus, Para-influenza 4, Coronaviruses NL63 & HKU1, Newly discovered viruses, Human metapneumovirus, Human bocavirus, Polyomaviruses, WU and KI – Mimivirus, Importance of newly discovered ALRTI causes, Requirements for further research